Mengenal masalah lingkungan global: Penipisan lapisan ozon di Stratosfer - Cahyani, Nadilah Dwi (Maliki Interdisciplinary Journal, 2024)
The atmosphere consists of 4 layers that we need to know, each layer has different physical properties such as pressure and type of gas. The first atmospheric layer is the troposphere closest to the earth. The second layer, namely the stratosphere, contains ozone which functions as a place to absorb ultraviolet light. The third layer is the mesosphere. The fourth layer is the thermosphere. In the stratosphere, the ozone layer is thinning, which is a significant global environmental issue, caused by the release of dangerous chemicals such as chlorofluorocarbons (CFCs), halons and other chemicals. The ozone layer functions to protect the earth from dangerous ultraviolet (UV) radiation. A decrease in ozone concentrations has been observed since the late 20th century, especially in the polar regions, with the most severe "ozone hole" phenomenon occurring in Antarctica. The impact of ozone depletion is causing skin cancer, eye damage, and disruption of marine and land ecosystems. Global efforts such as the Montreal Protocol have succeeded in reducing emissions of ozone-depleting substances, but restoration of the ozone layer will take a long time. Continued research and policy remain necessary to ensure success in protecting and restoring the ozone layer for future generations.